Impaired GAPDH-induced mitophagy contributes to the pathology of Huntington’s disease - Hwang, Sunhee (EMBO Mol Med, 2015)
Mitochondrial dysfunction is implicated in multiple neurodegenerative diseases. In order to maintain a healthy population of functional mitochondria in cells, defective mitochondria must be properly eliminated by lysosomal machinery in a process referred to as mitophagy. Here, we uncover a new molecular mechanism underlying mitophagy driven by glyceraldehyde-3-phosphate dehydrogenase (GAPDH) under the pathological condition of Huntington’s disease (HD) caused by expansion of polyglutamine repeats. Expression of expanded polyglutamine tracts catalytically inactivates GAPDH (iGAPDH), which triggers its selective association with damaged mitochondria in several cell culture models of HD. Through this mechanism, iGAPDH serves as a signaling molecule to induce direct engulfment of damaged mitochondria into lysosomes (micro-mitophagy). However, abnormal interaction of mitochondrial GAPDH with long polyglutamine tracts stalled GAPDH-mediated mitophagy, leading to accumulation of damaged mitochondria, and increased cell death. We further demonstrated that overexpression of inactive GAPDH rescues this blunted process and enhances mitochondrial function and cell survival, indicating a role for GAPDH-driven mitophagy in the pathology of HD.